Quantification of dissolved organic carbon at very low levels in natural ice samples by a UV-induced oxidation method - Preunkert, Susanne; Legrand, Michel; Stricker, P.; Bulat, S.; Alekhina, I.; Petit, J. R.; Hoffmann, Helene; May, B.; Jourdain, B. (Environmental science & technology, 2011)
The study of chemical impurities trapped in solid precipitation and accumulated in polar ice sheets and high-elevation, midlatitude cold glaciers over the last several hundreds of years provides a unique way to reconstruct our changing atmosphere from the preindustrial era to the present day. Numerous ice core studies of inorganic species have already evaluated the effects of growing anthropogenic emissions of SO2 or NOx on the chemical composition of the atmosphere in various regions of the world. While it was recently shown that organic species dominate the atmospheric aerosol mass, the contribution of anthropogenic emissions to their budget remains poorly understood. The study of organics in ice is at the infancy stage, and it still is difficult to draw a consistent picture of the organic content of polar ice from sparse available data. A UV oxidation method and IR quantification of CO2 was optimized to obtain measurements of dissolved organic carbon content as low as a few ppbC. Stringent working conditions were defined to prevent contamination during the cleaning of ice. Measurements in various ice cores corresponding to preindustrial times revealed dissolved organic carbon content of less than 10 ppbC in Antarctica and up to 75 ppbC in alpine ice.